ROSANA RUBIO Y FERNANDO NIETO (eds.) - Arquitectura de la soledad - Martín, Guiomar (ZARCH, 2025)
ROSANA RUBIO, FERNANDO NIETO (eds.)Arquitectura de la soledadEd. Asimétricas, Madrid, 2024, 248 pp. Tapa blanda. Idioma: español.  24 €ISBN 978-84-10065-09-3